Development and characterization of antitumoral electrospun polycaprolactone/functionalized Fe3O4 hybrid membranes. (September 2020) - Guadagno, L.; Raimondo, M.; Longo, R.; Sarno, M.; Iuliano, M.; Mariconda, A.; Saturnino, C.; Ceramella, J.; Iacopetta, D.; Sinicropi, M.S.
Abstract: The applicative potentiality of the nanotechnologies emerges more and more in all fields of science, technology, and medicine. In this context, magnetic nanoparticles have been recently proposed as promising nanomaterials to eliminate, through minimally invasive treatments, small tumours. This work deals with the design and realization of electrospun hybrid membranes of Polycaprolactone (PCL) incorporating magnetic nanoparticles modified with the acid citric-based ligand. The nature of the ligand allows very effective compatibility between nanoparticles and hosting fibers, as deducible by the nanoparticles distribution along the fibers. Dimension and functionalization of the nanoparticles, together with the optimization of the electrospinning parameters allow obtaining highly homogeneous distribution in the diameter of the nanocharged fibers, which ranges between 500 nm and 3 μm. The anticancer activity of the optimized electrospun hybrid membranes has been analyzed toward two different melanoma cell lines: the low metastatic A375 and the high metastatic A2058, using the MTT assay. The formulated membrane exhibited a dose-dependent reduction toward both melanoma cells viability, without a decrease of activity compared to the unfunctionalized Fe3 O4 nanoparticles. Promising results have been obtained also considering the antitumor activity of the hybrid Membranes toward uterine HeLa cells. Magnetic properties and structural and morphological characteristics of the functional membranes highlight very promising applications for tuning/enhancing the nanodelivery of drugs and chemotherapy assisted by electroporation technique. Graphical abstract: Image 1 Highlights: Magnetic nanoparticles are functionalized to enhance compatibility with the hosting polymeric matrix. They are dispersed in the polymeric solutions of PCL. Electrospinning parameters are selected to obtain optimized hybrid membranes. The functionalized nanoparticles result homogeneously distributed along the fibers of the membranes. The formulated membranes manifest anticancer activity toward melanoma and uterine HeLa cells.